Biogeografia histórica e estruturação de comunidades em lagartos neotropicais - Bezerra, Castiele Holanda (2024)
Community structure is result from several concomitant ecological processes, such as environmental filtering, species interactions, and historical evolutionary processes of dispersal, speciation, and extinction. The hypotheses that attempt to explain the processes that shape the current distribution patterns and co-occurrence of species and the assembly structure fall into two categories: ecological explanations, which involve the relationships of organisms with environmental climatic variables and interactions between species; and historical explanations, which concerned with the processes of change in the landscape over time and how lineages evolved in relation to these processes. However, understanding the role of each of these processes for different groups of organisms and in the different ecosystems is still a challenge to be resolved. The present thesis contain two chapters that attempt to help elucidate the processes responsible by the current patterns of diversity and distribution of lizard species in the Neotropical region, discussing the role of environmental variables and biogeographic and evolutionary processes in the structure of assemblages. The first chapter aims to investigate the temporal patterns of colonization of the Caatinga lizard fauna coming from adjacent biomes (Amazonia, Cerrado and Atlantic Forest), in order to understand the role of the Neogene geomorphological events and climate changes driving its diversification. In this chapter, we also analyze the role of the São Francisco River as historical riverine barrier, once this river has been widely pointed as the main barrier to the dispersal of species in this biome. In the second chapter we demonstrate how the use of different functional and phylogenetic diversity metrics, at different spatial scales, helped us to detect the processes responsible for structuring lizard communities in South America, in addition to pointing out their predictive power on the consequences of loss of diversity in communities facing climate change